2013
DOI: 10.1016/j.neuropsychologia.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Early gamma oscillations during rapid auditory processing in children with a language-learning impairment: Changes in neural mass activity after training

Abstract: Children with language-learning impairment (LLI) have consistently shown difficulty with tasks requiring precise, rapid auditory processing. Remediation based on neural plasticity assumes that the temporal precision of neural coding can be improved by intensive training protocols. Here, we examined the extent to which early oscillatory responses in auditory cortex change after audio-visual training, using combined source modeling and time-frequency analysis of the human electroencephalogram (EEG). Twenty-one e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 66 publications
6
39
1
3
Order By: Relevance
“…This study showed that the software as intervention allows the benefits seen in objective and biological changes. This finding was also found in two other studies in 2013: the first showed that the brain capacity in modifying itself through the stimulation could be seen in the evaluation of brainstem auditory evoked potential with speech stimuli, carried out pre and post CAT in two children diagnosed with APD, being this evaluation sensitive to changes by auditory stimulation 27 ; and another noted that the neuronal plasticity involves getting response with increased range while the oscillation of the activity related to temporal organization remains atypical 28 .…”
Section: Literature Reviewsupporting
confidence: 61%
See 1 more Smart Citation
“…This study showed that the software as intervention allows the benefits seen in objective and biological changes. This finding was also found in two other studies in 2013: the first showed that the brain capacity in modifying itself through the stimulation could be seen in the evaluation of brainstem auditory evoked potential with speech stimuli, carried out pre and post CAT in two children diagnosed with APD, being this evaluation sensitive to changes by auditory stimulation 27 ; and another noted that the neuronal plasticity involves getting response with increased range while the oscillation of the activity related to temporal organization remains atypical 28 .…”
Section: Literature Reviewsupporting
confidence: 61%
“…Heim et al 28 2013 CAT was performed five days in the week, for an average of 32 days with length of 100 minutes each session.…”
Section: Audio Training Software®mentioning
confidence: 99%
“…Abrams et al, 2009;Lehongre et al, 2011). Other studies showed specific processing deviances in individuals with language and literacy problems in the processing of higher oscillatory rates such as gamma rates (Heim et al, 2013;Hornickel et al, 2009). In addition, atypical cerebral lateralization has also been linked to cognitive dysfunction and disorders such as schizophrenia (Edgar et al, 2006;Groen et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, effectiveness is assessed using clinical methods that are vulnerable to experimenter bias, frequently rely on parent report, and often are not grounded in brain mechanisms. Prospective evaluative models should draw from examples in other fields, such as studies demonstrating that audiovisual training ameliorates deficits in early auditory γ power in children with language-learning impairment (Heim et al, 2013). A similar approach is warranted in ASD to directly address whether sensory interventions improve phase locking or power modulation.…”
Section: Diagnostic and Treatment Implications Of Oscillator Dysfmentioning
confidence: 99%